2010
DOI: 10.1097/sla.0b013e3181c35c87
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Circulating Mutant DNA in Unresectable Metastatic Colorectal Cancer

Abstract: This study suggests that the presence of circulating mutant DNA in unresectable MCRC patients, which can be detected using simple methods such as methylation-specific PCR or real-time PCR, is highly predictive of clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 27 publications
(60 reference statements)
1
40
0
Order By: Relevance
“…Lefebure et al detected, in the serum of unresectable MCRC, KRAS mutation andRASSF2A methylation and they observed that the presence of circulating mutant DNA was predictive of clinical outcome [68]. In a recent study was demonstrated the clinical utility of multiplex digital PCR to screen for multiple KRAS mutations in the plasma samples of MCRC patients [69] suggesting that the "liquid biopsy" is a feasible alternative to a solid tissue biopsy for identifying specific mutations.…”
Section: Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Lefebure et al detected, in the serum of unresectable MCRC, KRAS mutation andRASSF2A methylation and they observed that the presence of circulating mutant DNA was predictive of clinical outcome [68]. In a recent study was demonstrated the clinical utility of multiplex digital PCR to screen for multiple KRAS mutations in the plasma samples of MCRC patients [69] suggesting that the "liquid biopsy" is a feasible alternative to a solid tissue biopsy for identifying specific mutations.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…This is partly due to KRASmutation, which is currently assessed in the primary tumor. Many studies assessed mutation status in circulating tumor DNA, with the aim to improve patient selection [65], [66], [67] and [68].…”
Section: Colorectal Cancermentioning
confidence: 99%
“…[95][96][97] An analysis of 31 mCRC patients demonstrated that ctDNA detection (KRAS mutation and RASSF2A methylation) was highly predictive of clinical outcome under chemotherapy. 95 Median progression-free survival (PFS) was 5 months in patients positive for ctDNA versus 14 months in patients negative for ctDNA (p = 0.004). Separately, Spindler et al 96,97 developed a sensitive PCR method to quantitatively assess cfDNA as well as KRAS-and BRAF-mutated ctDNA in plasma.…”
Section: Monitoring Tumor Burden or Response During Treatmentmentioning
confidence: 99%
“…These findings may establish the basis for development of new therapies or biomarkers for metastatic non-resectable colorectal cancer. In particular, given the importance of the status of the KRAS gene for cetuximab therapy, it seems possible that other genes whose proteins are known to interact with the KRAS protein, such as C-raf [28] or RALGDS [29], may also be useful as biomarkers or as therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%